Psychological, clinical, and therapeutic predictors of the outcome of detoxification in a large clinical population of medication-overuse headache: A six-month follow-up of the COMOESTAS Project. (January 2019) - Bottiroli, Sara; Allena, Marta; Sances, Grazia; De Icco, Roberto; Avenali, Micol; Fadic, Ricardo; Katsarava, Zaza; Lainez, Miguel JA; Goicochea, Maria Teresa; Bendtsen, Lars; Jensen, Rigmor Højland; Nappi, Giuseppe; et al.
Aim: To identify factors that may be predictors of the outcome of a detoxification treatment in medication-overuse headache. Methods: Consecutive patients entering a detoxification program in six centres in Europe and Latin America were evaluated and followed up for 6 months. We evaluated anxious and depressive symptomatology (though patients with severe psychiatric comorbidity were excluded), quality of life, headache-related disability, headache characteristics, and prophylaxis upon discharge. Results: Of the 492 patients who completed the six-month follow up, 407 ceased overuse following the detoxification (non overusers), another 23 ceased overuse following detoxification but relapsed during the follow-up. In the 407 non-overusers, headache acquired an episodic pattern in 287 subjects (responders). At the multivariate analyses, lower depression scores (odds ratio = 0.891; p  = 0.001) predicted ceasing overuse. The primary headache diagnosis – migraine with respect to tension-type headache (odds ratio = 0.224; p  = 0.001) or migraine plus tension-type headache (odds ratio = 0.467; p  = 0.002) – and the preventive treatment with flunarizine (compared to no such treatment) (odds ratio = 0.891; p  = 0.001) predicted being a responder. A longer duration of chronic headache (odds ratio = 1.053; p  = 0.032) predicted relapse into overuse. Quality of life and disability were not associated with any of the outcomes. Conclusions: Though exploratory in nature, these findings point to specific factors that are associated with a positive outcome of medication-overuse headache management, while identifying others that may be associated with a negative outcome. Evaluation of the presence/absence of these factors may help to optimize the management of this challenging groups of chronic headache sufferers.